2013
DOI: 10.1007/s11120-013-9849-7
|View full text |Cite
|
Sign up to set email alerts
|

May photoinhibition be a consequence, rather than a cause, of limited plant productivity?

Abstract: Photoinhibition in leaves in response to high and/or excess light, consisting of a decrease in photosynthesis and/or photosynthetic efficiency, is frequently equated to photodamage and often invoked as being responsible for decreased plant growth and productivity. However, a review of the literature reveals that photoinhibited leaves characterized for foliar carbohydrate levels were invariably found to possess high levels of sugars and starch. We propose that photoinhibition should be placed in the context of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
161
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(170 citation statements)
references
References 93 publications
8
161
0
1
Order By: Relevance
“…decrease in Fv/Fm; [28] of chrysanthemum. Specifically, the highest level of irradiance had a significant negative effect on Fv/Fm at high temperatures.…”
Section: Maximum Photochemical Efficiency Of Psii (Fv/fm) Electron Tmentioning
confidence: 93%
See 1 more Smart Citation
“…decrease in Fv/Fm; [28] of chrysanthemum. Specifically, the highest level of irradiance had a significant negative effect on Fv/Fm at high temperatures.…”
Section: Maximum Photochemical Efficiency Of Psii (Fv/fm) Electron Tmentioning
confidence: 93%
“…Previous studies have shown that low irradiance protects the photosynthetic apparatus from the adverse effects of high temperature, while photoinhibition protects against both high irradiance and high temperature stress [7,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Abiotic stresses are able to disturb this balance, and affect especially CO 2 assimilation due to stomatal and biochemical limitations (Adams III et al, 2013). The degree of preservation of adequate synchrony between light harvest, energy conversion in photosystems and CO 2 assimilation, under stress conditions, is speciesdependent and important to plant productivity (Athanasiou et al, 2010;Kramer and Evans, 2011;Murchie and Niyogi, 2011;Yamori et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Plants display a set of acclimation strategies to maintain adequate photosynthesis rates in response to abiotic stress-inducers such as high temperature, drought and high light levels (Liu and Huang 2008;Chaves et al, 2009;Gonzalez-Cruz and Pastenes, 2012). To reach their potential or maximum photosynthesis, plants employ a fine metabolic coordination involving several inter-related processes, especially a close balance between photochemical activity and Calvin cycle reactions (Goh at al., 2012).Abiotic stresses are able to disturb this balance, and affect especially CO 2 assimilation due to stomatal and biochemical limitations (Adams III et al, 2013). The degree of preservation of adequate synchrony between light harvest, energy conversion in photosystems and CO 2 assimilation, under stress conditions, is speciesdependent and important to plant productivity (Athanasiou et al, 2010;Kramer and Evans, 2011;Murchie and Niyogi, 2011;Yamori et al, 2014).…”
mentioning
confidence: 99%
“…Stomatal restriction was reported as the main determinant of reduced photosynthesis under drought stress (Silva et al, 2013). The results showed that under limited irrigation treatment, the reduction in P n in different shading conditions did not coincide with reduction in C i , which indicate that the effect of shading treatments on photosynthesis under water stress conditions not only related to stomatal limitations in the leaves but also related to either damage in photosynthetic apparatus because of excess light absorption (Adams et al, 2013) or limited impairments in photophosphorylation, ribulose-1,5-bisphosphate carboxylase oxygenase (Rubisco) activity, and/or regeneration of ribulose-bisphosphate (Bota et al, 2004). Results demonstrated that the maximum photochemical efficiency of PSII (F v /F m ), probability of electron transport beyond QA (1-V J ) and the ratio of (1-V I )/ (1-V J ) which express the efficiency with which an electron from the intersystem electron carriers moves to electron acceptors in the reduced end at the PSI acceptor side, decreased due to limited irrigation, and this reduction was more pronounced under control treatment (no shade) compared with other shading treatments (Figure 3-a, b and c).…”
Section: Results and Discussion Gas Exchange Parameters And Photochemmentioning
confidence: 93%